Unpacking socio-demographic predictors of child aggression: insights from a Saudi Arabian context from parents’ and caregivers’ perspectives - Lone, Ayoob (Frontiers in Psychology, 2025)
Aggressive behavior in children is influenced by different sociodemographic factors. However, there is limited research on the impact of these factors on child aggression in Saudi Arabia. This study aimed to explore the sociodemographic factors associated with aggressive behavior among Saudi schoolchildren. A cross-sectional study was performed on 315 school-going children using stratified school selection with caregivers convenience sampling. Caregivers completed the Arabic caregivers-proxy version of the Buss Perry Aggression Questionnaire-Short form (BPAQ-SF). Multiple linear regression analysis was used to evaluate the association between various demographic variables and aggression. The significance level was set at a p < 0.05 throughout the analysis. The findings revealed a significant relationship between different sociodemographic variables and the BPAQ-SF. The results revealed that gender, age, family type, family occupation, parental education, and monthly income were found to be significant predictors of child aggression. Among these demographic factors, female gender (β = −0.15, p < 0.01), higher fathers (β = −0.19, p < 0.01), and mothers education (β = −0.47, p < 0.01) were associated with lower physical aggression scores. Verbal aggression was lower among children in nuclear families (β = 0.11, p < 0.05) and those with higher maternal education (β = −0.31, p < 0.01). Greater anger was observed among young children (<6 years; β = −0.24, p = 0.01), those with unemployed parents (β = −0.14, p = 0.01), lower paternal education (β = −0.19, p = 0.01), and maternal education (β = −0.29, p = 0.01), whereas extended family type showed a positive association with anger (β = 0.12, p = 0.05). Hostility was negatively related with maternal education (β = −0.25, p < 0.01) and monthly income (β = −0.15, p < 0.01). This study identified several demographic factors that played a role in the development of aggression in children. Thus, this study emphasizes that contributing factors should be considered when formulating and applying intervention strategies to manage aggressive behavior in children.